The influence of experience and modality of presentation (online vs. offline) on hypnotizability - Rasch, Björn; Cordi, Maren Jasmin (Frontiers in Psychology, 2024)
Hypnotizability is conceptualized as a stable personality trait describing the ability to respond to suggestions given under hypnosis. Hypnotizability is a key factor in explaining variance in the effects of hypnotic suggestions on behavior and neural correlates, revealing robust changes mostly in high hypnotizable participants. However, repeated experience and training have been discussed as possible ways to increase willingness, motivation and ability to follow hypnotic suggestions, although their direct influence on hypnotizability are still unclear. Additionally, it is important whether hypnotizability can be assessed reliably online. We investigated the influence of the degree of experience with hypnosis and the presentation mode (online versus live) on the stability of hypnotizability in two groups of 77 and 102 young, healthy students, respectively. The first group was tested twice with the Harvard Group Scale of Hypnotic Susceptibility (HGSHS) after two weeks. During this period, participants either repeatedly performed on a hypnosis or a progressive muscle relaxation or served as waiting control group. In the second group, participants performed both in an online or offline version of the HGSHS, with varying time intervals (1-6 weeks). Contrary to our expectations, hypnotizability declined from first to second assessment in the first group. The reduction was most prominent in initially highly hypnotizable subjects and independent of the experience intervention. We observed a similar reduction of hypnotizability in the second group, independent of presentation modality. The reduction was again driven by initially highly hypnotizable subjects, while scores of low hypnotizable subjects remained stable. The presentation modality (online vs. offline) did not influence HGSHS scores, but the test-retest reliability was low to moderate (rtt = 0.44). Our results favor the conclusion that generally, hypnotizability is a relatively stable personality trait which shows no major influence of pre-experience or modality of assessment. However, particularly highly hypnotizable subjects are likely to experience a decline in hypnotizability in a retest. The role of the concrete assessment tool, psychological factors and interval length are discussed. Future studies should replicate the experiments in a clinical sample which might have higher intrinsic motivation of increasing responsiveness towards hypnotic interventions or be more sensitive to presentationmode.